Art historiography and Bild-wissenschaft: new perspectives on some objects by the Venda sculptor, Phutuma Seoka - de Villiers-Human, Suzanne (Acta Academica: Critical views on society, culture and politics, 2012)
It is argued that the apparatus of western art history has been sharpened by the current media consciousness. Typical art historical tools are self-consciously harnessed in the process of scrutinising objects which resist and expand these methods and theories. The focus is on some objects of Venda polychrome sculpture which “took the South African art world by storm” in the 1980s when these specimens of rural craftsmanship in wood were deemed fit to enter the gallery circuit. An analysis of the Venda sculptors’ religious and social knowledge of the use of patterned decoration on ritual tools in wood, and of performances by firelight of myths of origin with wooden dolls during initiation rituals, informs my alternative interpretation of the modern polychrome sculptures steering away from issues of cross-cultural aesthetics, the dialectic of modernism and traditionalism and post-colonial studies. Rather, I interpret the works as medium-self-conscious objects which extend their own cultural and social agency to communicate more widely to a non-initiate audience which may include visitors to an art museum. This shift of focus from a history of art to a history of media effects an altered perspective on the objects themselves and on the methods used to interpret them.